Entre discursos e práticas: a construção da confiança nas interações professor-alunos - Paschoal, Claudia Lucia Lessa (2010)
This study investigated the role of confidence in the future and in life, in the discursive-texts of teachers and students, and the possible effects of meaning in the construction of the students professional identity, more specifically, the way they see the world, the future and themselves within this world. The accelerated development of information and communication technologies has determined new social, economic and cultural settings and reproduces a mass culture where prevails the mechanical logic and such increasingly fragmented human beings and their seizure in the world, especially their ability to reflection. Believing in collective spaces as places of interaction and creation of all the aspects related to humans and therefore the only possibility of transforming the social reality in which humanity lives, it uses the theoretical subsidies offered by the Social-Discursive Interactionism, the Theory of Communicative Action and the Theory of Complexity in Applied Linguistics. The intersection point between them is a singular human being with endless potential for emancipation, because of the language he uses and his ability to represent the multiple realities that he experiences. Starting out with this point of view, a field research was carried out in a public institution dedicated to professional education. The research was built on the assumptions that language actions materialize representations of confidence that teachers have about the work in the world, their own profession, and the future life and that the students identity formation for the future and work in the world is influenced by experienced trust and shared in the actions of language between them and teachers. Data were collected through questionnaires and interviews with four teachers and eight teenage students from the Technical Course on Building Integrated High School. The proceedings of data analysis (mainly qualitative) derive from the intercrossing of modal marks and representations of the formal worlds, according to Habermas (1987 apud BRONCKART, 2003) and how they suggest the teacher s acts: the communicative or the instrumental one, and then, analyze the students discursive-texts in search of the effects of the teachers actions. The results indicate that only modal marks do not necessarily give a certain kind of acting teacher, and that living with the instrumental and communicative actions allows students to learn how to cope with the complexity of life.